Programas de ginásticas e níveis de habilidades motoras em crianças - Silva, Ana Carolina Fernandes da (Universidade Federal do Tocantins, 2021)
The development of motor skills from childhood builds a fertile ground for the continuation of the children's development process. With that, Gymnastics allows for integral development from early childhood, promoting the development and learning of basic and specific skills and the child's social inclusion. In this sense, the aim of this study was to verify the influence of gymnastics programs on the levels of motor skills in children. It was defended the hypothesis that children who participate in gymnastics programs present higher levels of motor skills at the end of the intervention, when compared to the levels presented before participating in the program. For this, a literature search was carried out in three SciELO databases, VHL Regional Portal and Capes Journal Portal, from April 5, 2021 to May 26, 2021, generating 485 articles in the search and after applying the filters ( publications in the last ten years, Portuguese languages and keyword crossing) 13 articles were selected that contemplated the objective of the study. After the analysis, it was identified that the results are similar among those who performed interventions and/or only analyzed the development of children, demonstrating an evolution in motor skills after the initial and final tests. With this, it is understood that children, when submitted to well-structured proposals that stimulate motor development in different environments, tend to evolve more than those who arejust inserted in unstructured activities.